Antibiotic resistance of the most common bacteria isolated in blood cultures. Neonatal intensive care unit. Hospital III-1. Chiclayo, Perú 2020-2021 - Sosa-Flores, Jorge Luis (2025)
Introduccion: Bacterial resistance to antibiotics is associated with increased morbidity and mortality. Objective: Determine the antibiotic resistance of the most common bacteria isolated in blood cultures in a Neonatal Intensive Care Unit. Materials and methods: Descriptive – retrospective, the identification of bacteria was done with VITEK XL, the susceptibility was done with the CLSI M100 guidelines. 30 edition. Results: The antibiotic resistance of the isolated bacteria was: Imipenem 15.6%, Meropenem 14.3%, Piperacillin/tazobactam 9.4%, Vancomycin 8.5%, Colistin 7.7%, Quinupristin/dalfopristin 7.1%, Amicacin 6.7%, Linezolid 2.7%. Tigecycline, Nitrofurantoin, Ertapenem, Tobramycin, Chloramphenicol, Streptomycin, Gentamicin had 0% resistance. The ECN had resistance to vancomycin 7.9%, Quinupristin/dalfopristin (6.4%), Linezolid (2.8%). Tigecycline, Nitrofurantoin, Doxycycline and Chloramphenicol had 0% resistance. Klebsiella pneumoniae: 0% resistance to Amicacin, meropenem, gentamicin, tigecycline, ertapenem, imepenem, colistin and piperazine/Tazobactan. Acinetobacter baumannii: 0% antibiotic resistance, for Gentamicin, Ciprofloxacin, Tigecycline, Colistin, Levofloxacin and Tobramycin. Conclusion: The antibiotics with 0% resistance to all bacteria were Tigecycline, Nitrofurantoin, Ertapenem, Doxycycline, Tobramycin, Chloramphenicol, Tobramycin, Chloramphenicol, Gentamicin.